Design and methods of a multicenter randomized clinical trial of effects of diabetes-educated psychologist on glucose management and diabetes distress - Zeijlemaker, Johanna; Anderbro, Therese; Sterner Isaksson, Sofia; Lind, Marcus (Frontiers in Clinical Diabetes and Healthcare, 2025)
IntroductionMany people with type 1 diabetes struggle to manage their glucose levels and experience stress related to the behavioral demands of the disease. The aim of this study is to investigate whether treatment with a diabetes-educated psychologist can improve glucose levels and decrease diabetes distress.Materials and methodsIndividuals with HbA1c >62 mmol/mol (7.8%) were randomized to either psychological treatment or control group. The study duration for each participant was 52 weeks. Patients who received treatment met with a diabetes-educated psychologist a minimum of seven times. In total 6 outpatient diabetes units and 10 psychologists participated. Cognitive behavioral therapy was primarily the treatment of choice. Both groups met with a diabetes nurse and/or physician at the start of the study and at 3, 6, and 12 months. HbA1c, blood pressure, and weight were measured at scheduled visits. Diabetes distress, quality of life, hypoglycemia confidence, and treatment satisfaction were evaluated using questionnaires. The primary endpoint is the difference in HbA1c from baseline to week 52. Secondary endpoints are changes in diabetes distress and quality of life from baseline to week 52, as well as treatment satisfaction at 52 weeks.DiscussionThis study seeks to improve knowledge about how to support patients who struggle to manage their diabetes. If the results of this study show that psychological treatment has an effect on HbA1c or on diabetes distress, it could indicate that psychologists should become more involved in diabetes care teams. Clinical trial registration: ClinicalTrials.gov ID NCT03753997